Exploring and analysing sources of technical efficiency in water supply services: Some evidence from Southeast Asian public water utilities - See, Kok Fong (Water resources and economics, 2015)
This is the first efficiency analysis of Southeast Asian water utilities that uses a double bootstrap data envelopment analysis model. A sample of 40 publicly owned water utilities was selected in the study. Six explanatory factors (i.e., non-revenue water, population density, gross domestic production per capita, average maximum temperature, dummies for state-owned enterprises and groundwater extraction) have been used to explain the differences in the technical inefficiency effects across public water utilities in Southeast Asia. We find that Southeast Asian water utilities, on average, obtained a technical efficiency of 0.74. The result reveals that the population density is linked with the technical inefficiency in the reverse direction. Furthermore, we also observe that state-owned water enterprises perform slightly lower than those from other forms of publicly-owned water utility. Policy implications are derived.